Intramural platelet deposition in cerebral vasculopathy of systemic lupus erythematosus. Issue 1 (January 1993) - Ellison, D; Gatter, K; Heryet, A; Esiri, M
Abstract : AIMS: To test the hypothesis that fragments of platelet thrombi and vascular endothelium are incorporated into the walls of small cerebral vessels in systemic lupus erythematosus (SLE). METHODS: Six varied necropsy cases of central nervous system (CNS) SLE and 15 controls were studied. The controls were selected to represent a wide range of diseases in which the cerebral circulation is compromised. Tissue sections were stained by standard histochemical and immunocytochemical methods, the latter using antibodies to platelet membrane glycoprotein IIIa (CD61), and vascular endothelium (CD31). RESULTS: In four of six cases of CNS SLE characterised by small vessel hyalinization and thickening, fragments of platelet membrane were found in the walls of small cortical and meningeal vessels. Similar findings were not evident in two other SLE cases that were characterised by relatively short clinical histories and an acute vasculitis. One control case of severe polyarteritis nodosa showed platelet fragment deposition in arteries larger than the vessels so affected in SLE. CONCLUSIONS: Previous studies have suggested that neuropsychiatric symptoms in SLE may be related to repeated episodes of vasculitis in small cerebral vessels that are triggered by antiphospholipid antibodies. Concurrent thrombus formation might facilitate the incorporation of platelet fragments into small vessel walls. This process contributes to the thickening and irregularity of small vessels, a major feature of longstanding cases of CNS SLE.